Subjective Well Being Anak Korban Kekerasan dalam Rumah Tangga (KDRT) - Tri Putri; Herman Nirwana; Afdal Afdal (Jurnal Neo Konseling, 2021)
The happiness of children and teenager is an inseparable part of family happiness. Family is one of the factors in the determinant of children and teenager. Children living in families experiencing domestic violence are at high risk for mental health problems, such as depression and life failure. This study aims to describe the subjective well being of children victims of domestic violence based on two aspects, namely aspects of life satisfaction and aspects of affection (positive and negative experiences). This study uses a descriptive approach with a sample of 53 students with the characteristics of adolescents who are violent in the household. The sampling technique used is purposive sampling and the data collection tool uses a subjective well being scale. The results of the study revealed that the subjective well being of children victims of domestic violence was low with a percentage of 49.06%, while in the medium category with a percentage of 35.85%, high category 13.21%, and very low category 1.89%. The implication of this research is the basis for guidance and counseling teachers to improve the subjective well-being of students in schools.